Konsumsi Makanan Jajanan, Konsumsi Makanan di Rumah dan Status Gizi Anak di SDN 04 Petang, Jakarta Timur - Simanjuntak, Getruida; Hartono, Anton Sri (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
AbstractNutrition problems still becomes a problem in developing countries and developed countries. In Indonesia, since 1950 there have been concerns that malnutrition can affect to development childrens. The growth and brain development of children requires very important nutrients such as carbohydrates, proteins, fats, vitamins, minerals and water. Therefore recommended dietary alowance (RDA) can be determined by the average requirement of nutrient to achieve the optimal nutritional status.The purpose of this study was to determine the relationship between the consumption of snack foods, food consumption at home and nutritional status in student public elementary school 04 PETANG, East Jakarta.The total sample of this study is 60 students. This study used t-test to analyzing the data. This analysis is used to determine the relationship between the characteristics (age, mother’s education, mother’s occupation, family income, pocket money, snack foods), food intake of snacks and food consumption at home and nutritional status. The results shows no significant relationship between average of Z-score (BMI/U) of children by age, mother’s education, mother’s occupation, family income, pocket money for snacks and snack foods (p>0.05). However, this study found that there is a relationship between intake of energy (r=0.682), protein (r=0.689) and Z-score (BMI/U) of children (p<0.05).Keywords: snack foods, food consumption, nutritional statusAbstrakSampai saat ini gizi menjadi masalah baik di Negara berkembang maupun Negara maju. Di Indonesia sejak tahun 1950 sudah terdapat kekhawatiran bahwa gizi buruk dapat mempengaruhi perkembangan anak. Dalam pertumbuhan dan perkembangan otak anak dibutuhkan zat-zat gizi yang sangat penting yaitu karbohidrat, protein, lemak, vitamin, mineral dan air oleh karenanya Angka Kecukupan Gizi (AKG) dapat menentukan rata-rata kecukupan yang dianjurkan guna mencapai status gizi yang optimal. Tujuan dari penelitian ini adalah mengetahui hubungan antara konsumsi makanan jajanan dan konsumsi makanan di rumah terhadap status gizi anak sekolah dasar. Populasi dalam penelitian ini adalah siswa SDN 04 Petang, Jakarta Timur. Sedangkan sampelnya sebanyak 60 orang. Analisis data pada penelitian ini dengan menggunakan uji t. Teknik ini digunakan untuk mengetahui hubungan antara karakteristik (umur, pendidikan ibu, pekerjaan ibu, pendapatan orangtua, uang jajan dan jenis makanan jajanan), asupan makanan jajanan dan makanan di rumah dan status gizi. Hasil uji statistik menunjukkan tidak adanya perbedaan yang bermakna rata-rata Z-score (IMT/U) anak berdasarkan umur, pendidikan ibu, pekerjaan ibu, pendapatan orangtua, uang jajan dan jenis makanan jajanan. Hubungan Z-score (IMT/U) anak dengan asupan energi (r=0,682;p<0,05) dan protein (r=0,689;p<0,05) sangat bermakna.Kata kunci: makanan ringan, konsumsi makanan, status gizi